Chapter 5 Migrant Women in Trade Unions Domestic Service Activism in France - Le Petitcorps, Colette (Studies in Migration and Diaspora, 2018)
This chapter analyses the way in which migrant women employed in the domestic services sector in France make their work political. The French context encompasses a double reality. On the one hand, the state promotes a regularized market and the professionalization of paid care work performed in the home. On the other hand, the fact that a majority of domestic sector workers are migrant women leads to the reproduction of working conditions which display continuities with more ancient forms of domestic services relations. In this context, migrant women's demands in trade unions for domestic workers often prove contradictory, ambivalent and different according to their different work experiences. I address the complexity of this form of activism through the analysis of in-depth interviews realized with two migrant women activists involved in different trade unions over different periods. The first one, of Mauritian origin, fought alongside undocumented domestic workers in the early nineties. The second, of Ivoirian origin, has been involved since 2011 in struggles against the exploitation of registered child-minders. Drawing on fieldwork data, I examine the process through which migrant domestic workers create new political subjectivities, and their potential for contesting the norms regulating domestic work, traditional conceptions of citizenship and dominant gender relations.